Kualitas Fisik Telur Ayam Ras dengan Pelapisan Bahan Herbal Selama Penyimpanan - Saputri, Kade Wahyu; Nur’aini, Nur’aini; Marhamah, S. (Universitas Bengkulu, 2024)
Chicken eggs will experience a decrease in quality during storage. Egg preservation methods are needed to maintain egg quality and extend shelf life. This research evaluated the effect of coating egg shells using herbal solutions during storage on egg white index, egg yolk index, egg white pH, egg yolk pH and air sac depth. The research method used a completely randomised design with 2 treatment factors and 4 replications. The first treatment factor was eggshell coating consisting of 4 levels, namely control, lemongrass solution, kaffir lime leaf solution and pandan leaf solution. The second treatment factor is storage time, which consists of 5 levels, namely 0, 5, 10, 15, and 20 days. Data were analysed using ANOVA with Tukey's advanced test at a significance level 0.05. The research showed that the eggshell coating method using herbal ingredients and cold storage maintained the physical quality of purebred chicken eggs during 20 days of storage compared to the control treatment at room temperature. Coating herbal ingredients using lemongrass solution is the best herbal ingredient with the lowest egg white index, egg yolk index, egg white pH, egg yolk pH and air sac depth.